Política y sociedad en el Perú : cambios y continuidades - Cotler, Julio (Lima : IEP, 1994)
"Collection of articles by one of the most original political scientists in Peru covers 30 years of sociopolitical thought. Describes a time of great social change which saw the invalidation of traditional social stratification based on a colonial criteria of ethnicity, the creation of new social and political institutions, and the development of new public expectations of the State. Concludes, in part, that the great inequalities based on ethnicity and class have not disappeared and that the country still faces the challenge of building a democratic and cohesive society"--Handbook of Latin American Studies, v. 57.
Includes bibliographical references (páginas229-235).
Descripción basada en recurso en línea; Título de la página del título en PDF (e-libro, visto November 17, 2014).
Recurso electrónico. Santa Fe, Arg.: e-libro, 2015. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a e-libro.
Keywords: Peru -- Politics and government -- 1968-1980.; Perú -- Política y gobierno -- 1968-1980.; Peru -- Politics and government -- 1980-; Perú -- Política y gobierno -- 1980-; Peru -- Social conditions -- 1968-; Perú -- Condiciones sociales -- 1968-; Libros electrónicos.